MARKETING STRATEGY OF CATFISH THROUGH AGRIBUSINESS SUBSYSTEM IN THE PEGUYANGAN ECOTOURISM AREA, NORTH DENPASAR - I Gusti Ngurah Sugiana; Dewa Nyoman Sadguna; Kadek Johan Okan Adnyana; Ngurah Agus Crisna Arya Budiarsa (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The purpose of this study was to determine the appropriate marketing strategy used by Pokdakan Mina Mandiri in each agribusiness subsystem by analyzing it through the SWOT Matrix through strengths, weaknesses, opportunities and challenges. This study used a descriptive method by determining the location by purposive sampling with the consideration that the research location had been keeping catfish for a long time through the upstream, middle and downstream agribusiness subsystems. The results of the SWOT analysis show that the position of the cultivator for the upstream agribusiness subsystem is in quadrant III Turn Around/Stability (Change Strategy) followed by the SWOT matrix so that the right strategy is obtained which is the WO Strategy which is taking advantage of existing opportunities by improving the internal weaknesses of members of the Mina Mandiri group. So that the marketing strategy: (1) Cultivators to be able to increase business capital from loans, (2) cultivators to be able to make alternative feeds, (3) cultivators to find alternative markets other than the local market, and (4) cultivators to take advantage of local government policies that support hatchery activities. For the middle agribusiness subsystem, it is in quadrant I with an aggressive SO strategy Marketing strategy using internal strengths to take advantage of opportunities from group members, so that the marketing strategy: (1) Cultivators to maintain quality, quantity and continuity of products according to demand, (2) cultivators in determining prices to be competitive, (3) cultivators to maintain good relations with sellers, and (4) cultivators to improve facilities and infrastructure by utilizing natural resources. For the downstream agribusiness subsystem, the cultivator's position is in quadrant IV of the defensive marketing strategy (WT) by taking advantage of internal weaknesses to reduce external threats, so that the marketing strategy: (1) Cultivators to add manpower to process catfish, (2) cultivators to be able to make products preparations that have a longer shelf life, (3) cultivators to be able to increase their consumption of catfish products, (4) cultivators to see competitors as competitors, and (5) cultivators to improve the packaging of their processed products.